2016
DOI: 10.1111/joic.12286
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Left Judkins Catheter as a Single Multipurpose Catheter in Transradial Coronary Angiography From Right Radial Artery: A Randomized Comparison With Conventional Two‐Catheter Strategy

Abstract: In TRA from RRA, JL3.5 catheter can be very effective when dedicated multipurpose catheter is not available. As a single multipurpose catheter, JL works perfectly in nearly half of procedures without prolonging procedure and fluoroscopy times. However insisting on a single-catheter approach with JL could unnecessarily increase fluoroscopy time and, hence, radiation exposure. (J Interven Cardiol 2016;29:257-264).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 15 publications
2
24
0
Order By: Relevance
“…Of those, 28 articles were excluded because either no RAO/UAO rates were reported or they were reviews/editorials or meta‐analyses not reporting original data on RAO/UAO rates, whereas 5 studies were excluded because they were duplicate reports (Figure ). Finally, 112 original articles assessing RAO and/or UAO were deemed eligible for our meta‐analysis, of which 99 cohorts from 92 studies publishing RAO…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of those, 28 articles were excluded because either no RAO/UAO rates were reported or they were reviews/editorials or meta‐analyses not reporting original data on RAO/UAO rates, whereas 5 studies were excluded because they were duplicate reports (Figure ). Finally, 112 original articles assessing RAO and/or UAO were deemed eligible for our meta‐analysis, of which 99 cohorts from 92 studies publishing RAO…”
Section: Resultsmentioning
confidence: 99%
“…Ultrasonography demonstrated clear superiority over clinical evaluation with respect to RAO and UAO detection rates. Absence of flow on Doppler ultrasonography along with the simultaneously obtained anatomic information (eg, thrombus delineation) appears as a straightforward detection technique of RAOs and UAOs. In this regard, the predictive accuracy of solely anatomic stenosis or partial flow remains to be established.…”
Section: Discussionmentioning
confidence: 99%
“…Louvard et al reported high success rates with left Amplatz catheter. Similarly JL catheter was reported to be effective as a single transradial catheter …”
Section: Introductionmentioning
confidence: 95%
“…Similarly JL catheter was reported to be effective as a single transradial catheter. [13][14][15] The purpose of our study was to evaluate the safety and efficacy of specialized hand-modified "Jacky-like" catheter (JLC) modified from 5F JL3.5 that is used as a single dual-purpose catheter compared with traditional 2-catheter (2C) approach with JL and right Judkins (JR) catheters, in patients undergoing diagnostic CAG through right radial artery (RRA). We also aimed to show that JLC is useful and safe as original Jacky catheter in reducing the time of the procedure and making catheter exchange unnecessary.…”
Section: Introductionmentioning
confidence: 99%
“…Similary in this larger context, the question of whether universal catheters shapes are actually “ideal” should be considered on evolving evidence base. Various reports including prospective randomized trials have described successful use of different “universal” catheters during TRA such as Tiger, Jackie, Kimny, Ikari, Fajadet, Amplatz or MAC 3.5 to reduce procedure time, fluoroscopy time, risk of radial irritation, spasm, pain, and access switchover. Erden's approach to re‐shaping guides may be more relevant to labs in settings where inventory or resources are more limited.…”
mentioning
confidence: 99%